Traumatic Dissection of Arterial Cervical Vessels: Report of Two Cases and Literature Review - Finger, Guilherme; Nascimento, Tobias Ludwig do; Tessaro, Julia Carolina Lusa; Stefani, Eduarda Tanus; Gripa, Maria Eduarda Conte; Tisbierek, Eduardo Ekman; Marrone, Luiz Carlos Porcello; Rynkowski, Carla Bittencourt (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2020)
Even though traumatic dissection of cervical arterial vessels is the major cause of stroke among adults, it is still an underdiagnosed disease in neurosurgical emergencies, since most patients do not have or present subtle clinical signs in the acute phase. The authors report two interesting cases of cervical artery dissection with different traumatic mechanisms and present a broad literature review about this subject.
Keywords: internal carotid dissection; vertebral artery dissection; cerebrovascular trauma